ANALISIS PERPANJANGAN MASA JABATAN KEPALA DESA DI TINJAU DARI PERSPEKTIF POLITIK HUKUM - NIM. A1011211058, LUHER (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This research examines the Analysis of Extension of Term of Office of Village Heads Reviewed from the Perspective of Legal Politics. The main focus of the problem in this study is How the Legal Politics Determine the Term of Office of Village Heads in the History of Legislation in Indonesia. The purpose of this study is to analyze the Legal Politics of Determining the Term of Office of Village Heads in the History of Legislation in Indonesia and to analyze the Ideal Term of Office of Village Heads to ensure the effectiveness and sustainability of leadership at the village level. This study uses a normative legal research methodology whose research nature uses a descriptive analysis approach. Data were obtained through literature studies, legislative approaches and analysis of related legal documents. The results of the study show that the regulation of the term of office of the village head has undergone various changes, starting from Law Number 5 of 1979 concerning Village Government by setting the term of office of the village head at 8 years and can be re-elected for 1 term, Law Number 22 of 1999 concerning Regional Government which changes the term of office of the village head to 10 years in 1 period and can be re-elected once, Law Number 32 of 2004 concerning Regional Government returns the term of office of the village head to 6 years and can serve a maximum of 2 terms, Law Number 6 of 2014 concerning Villages sets the term of office of the village head to 6 years with a maximum of 3 consecutive or non-consecutive terms, to Law Number 3 of 2024 concerning Villages sets the term of office of the village head to 8 years with a maximum of 2 terms. These changes reflect the dynamics of village government needs, political stability and regional goals, with the expected achievement being the creation of a democratic, stable village government that is able to improve community welfare. Keywords: Legal politics; Term of office; Village head.